Em busca da cidade moderna: as ações de saúde, de higiene e as intervenções urbanas em São Paulo durante a gestão de Antonio da Silva Prado (1899 1910) - Maestrini, Karla Aparecida (2015)
This dissertation seeks to undertake an analysis of the actions and health practices developed in São Paulo during the years 1899 to 1910. This period corresponds to administration of the first mayor of São Paulo, Antonio da Silva Prado, a conservative man, member one of the most traditional families of São Paulo aristocracy. During the years before the establishment of the prefecture, the actions relating to hygiene and public health were in charge of the administration of the Municipality of São Paulo and its Quartermaster Police and Hygiene. Supported on the remaining administrative structure of the old intendancies the counselor Prado, to assume the newly created municipality, opened the implementation of the modern city project to São Paulo. In these terms, Meadow sought to bring "European feel" for the metropolis in accelerated development process, in the late nineteenth to the twentieth century, aiming to make it a city ruled and ordered the point of view of its material development. Thus, we seek to understand the role played by health and urban actions in the implementation of city project for the state capital, noting the arising conflicts and clashes between the local authority and certain constituencies the São Paulo population facing the interventions promoted in the public space